1981
DOI: 10.1111/j.1095-8649.1981.tb05830.x
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout, Salmo gairdnerii Richardson, spermatozoa: effects of cations and pH on motility

Abstract: Earlier work on the factors influencing inhibition of activation of the spermatozoa of Salmo gairdnerii has been confirmed. Diluents containing K+ and of pH less than 7.8 do not activate the spermatozoa. The presence of Na+ in the diluent has a mildly antagonistic effect on this inhibition. It has now been demonstrated that both CaZ+ and Mg2+ markedly antagonize the inhibition due to low pH and K+. It is suggested that inhibition due to potassium salts could account for the inhibition previously attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
2
5

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(93 citation statements)
references
References 9 publications
8
78
2
5
Order By: Relevance
“…Generally, interactions of ions present in the seminal fluid with the sperm membrane do influence the membrane potential [12] and represent a mechanism of inhibition of spermatozoa in the seminal fluid or sperm duct [8] , allowing the maintenance of the potential of motility before release to the surrounding medium [29] . According to past data, it was revealed that the low K + levels of surrounding medium is key factor for activation of salmonid fish spermatozoa [4,29] , also the increase of semen pH may be responsible for acquisition of motility of spermatozoa in the rainbow trout Oncorhynchus mykiss and chum salmon, Oncorhynchus keta [7,26,27] during passage of spermatozoa from the testis to the spermatic duct i.e., before sperm ejaculation to spawnig medium (water).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, interactions of ions present in the seminal fluid with the sperm membrane do influence the membrane potential [12] and represent a mechanism of inhibition of spermatozoa in the seminal fluid or sperm duct [8] , allowing the maintenance of the potential of motility before release to the surrounding medium [29] . According to past data, it was revealed that the low K + levels of surrounding medium is key factor for activation of salmonid fish spermatozoa [4,29] , also the increase of semen pH may be responsible for acquisition of motility of spermatozoa in the rainbow trout Oncorhynchus mykiss and chum salmon, Oncorhynchus keta [7,26,27] during passage of spermatozoa from the testis to the spermatic duct i.e., before sperm ejaculation to spawnig medium (water).…”
Section: Discussionmentioning
confidence: 99%
“…21,22) Trout spermatozoa do not move in the presence of EGTA22) or in the presence of Ca 21-channel blockers. 22,23) Moreover, upon the initiation of movement of sper matozoa, an increase occurs in the intracellular concentra tion of Ca2+ ions in these cells.24,25) These data strongly suggest that external Ca2+ ions might be involved in the in itiation of flagellar movement in salmonid spermatozoa.…”
Section: Discussionmentioning
confidence: 96%
“…Suppression of sperm motility in acidified activating solutions has also been observed for many teleost species. 21,[30][31][32] Redondo-Miiller et al9) reported that milt spermatozoa from carp, with a low potential for movement, acquired motility during 30-minute incubation in K+ rich (150-200 mM KCl) solutions in a pH-independent manner. The minimal level of K + ions for the acquisition of motility was 50mM in a solution of 380 mOsm/kg.…”
Section: Discussionmentioning
confidence: 99%
“…, and Mg +2 at increased concentrations were antagonistic to K + ions (Scheuring 1925, Baynes et al 1981 but were indispensable to initiate sperm motility (Christen et al 1987, Cosson et al 1989, Billard et al 1995, Krasznai et al 2000, Bondarenko et al 2014 In our studies on brook trout spermatozoa the concentration of ions in the water used for activation was diversifi ed (Table 1 (Billard et al 1995, Lahnsteiner et al 1998, Glogowski et al 2000. It is therefore possible that the increased concentration of K + , Na + , and Ca +2 ions in the water of 10.0‰, though smaller than in the salmonid seminal plasma, does not have to be the reason for the decrease in the values of the studied sperm motility parameters.…”
Section: +2mentioning
confidence: 99%